2018
DOI: 10.3390/en11113171
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Load Flow Method Based on Modified Latin Hypercube-Important Sampling

Abstract: The growing amount of distributed generation has brought great uncertainty to power grids. Traditional probabilistic load flow (PLF) algorithms, such as the Monte-Carlo method (MCM), can no longer meet the needs of efficiency and accuracy in large-scale power grids. Latin Hypercube Sampling (LHS) develops a sampling efficiency and solves the correlation problem of distributed generation (DG) access nodes for accuracy analyses. In this paper, a modified Latin Hypercube-Important Sampling method is proposed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…LHS sampling [30,31] Suitable for uniform sampling in multi-dimensional space and small samples; high sampling efficiency…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LHS sampling [30,31] Suitable for uniform sampling in multi-dimensional space and small samples; high sampling efficiency…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, Latin hypercube sampling (LHS) is considered to be an improvement on rough MCS. In [30], LHS is used to improve sampling efficiency and deal with the relevance problem of DRE generation access nodes, while the methods of MCS and LHS are analyzed to generate WP scenarios in [31]. At present, many scholars have verified that the copula function in statistical science is effective in the correlation modeling between random variables.…”
Section: Power Uncertaintymentioning
confidence: 99%
“…In view of the advantages of the LHS method, some scholars have used this method to model randomness problems. Li, Q. et al proposed an improved LHS method applied to the grid system with distributed generation, which improved the efficiency and accuracy of the probabilistic power flow algorithm [43]. Zhao, W. et al proposed an LHS method suitable for random variables and demonstrated the superiority of the proposed method by comparing the computational performance of Monte Carlo (MC) continuous sampling, MC non-continuous sampling, and the proposed method [44].…”
Section: Latin Hypercube Samplingmentioning
confidence: 99%
“…Some of these new methods include the fast continuation method, the extended Newton-Raphson method, the extended current injection load flow method, the extended backward & forward sweep [17], etc. [14][15][16][17][18][19]. All those methods are increasing the coplexity of the problems.…”
Section: Introductionmentioning
confidence: 99%